Role of peripheral blood MRD and 18F-FDG PET in the post-CAR relapse setting: a case study of discordant peripheral blood and bone marrow MRD. Issue 2 (27th February 2023) - Schultz, Liora; Davis, Kara Lynn; Walkush, Ann; Baggott, Christina; Erickson, Courtney; Ramakrishna, Sneha; Aftandilian, Catherine; Lacayo, Norman; Nadel, Helen Ruth; Oak, Jean; Mackall, Crystal L
Abstract : Background: Chimeric antigen receptor (CAR) T cell therapy is an effective salvage therapy for pediatric relapsed B-cell acute lymphoblastic leukemia (B-ALL), yet is challenged by high rates of post-CAR relapse. Literature describing specific relapse patterns and extramedullary (EM) sites of involvement in the post-CAR setting remains limited, and a clinical standard for post-CAR disease surveillance has yet to be established. We highlight the importance of integrating peripheral blood minimal residual disease (MRD) testing and radiologic imaging into surveillance strategies, to effectively characterize and capture post-CAR relapse. Main body: Here, we describe the case of a child with multiply relapsed B-ALL who relapsed in the post-CAR setting with gross non-contiguous medullary and EM disease. Interestingly, her relapse was identified first from peripheral blood flow cytometry MRD surveillance, in context of a negative bone marrow aspirate (MRD <0.01%). Positron emission tomography with 18F-fluorodeoxyglucose revealed diffuse leukemia with innumerable bone and lymph node lesions, interestingly sparing her sacrum, the site of her bone marrow aspirate sampling. Conclusions: We highlight this case as both peripheral blood MRD and 18F-fluorodeoxyglucose positron emission tomography imaging were more sensitive than standard bone marrow aspirate testing in detecting this patient's post-CAR relapse. Clinical/Biologic Insight: In the multiply relapsed B-ALL setting, where relapse patterns may include patchy medullary and/or EM disease, peripheral blood MRD and/or whole body imaging, may carry increased sensitivity at detecting relapse in patient subsets, as compared with standard bone marrow sampling.